2013
DOI: 10.1371/journal.pone.0057254
|View full text |Cite
|
Sign up to set email alerts
|

12/15-Lipoxygenase-Derived Lipid Metabolites Induce Retinal Endothelial Cell Barrier Dysfunction: Contribution of NADPH Oxidase

Abstract: The purpose of the current study was to evaluate the effect of 12/15- lipoxygenase (12/15-LOX) metabolites on retinal endothelial cell (REC) barrier function. FITC-dextran flux across the REC monolayers and electrical cell-substrate impedance sensing (ECIS) were used to evaluate the effect of 12- and 15-hydroxyeicosatetreanoic acids (HETE) on REC permeability and transcellular electrical resistance (TER). Effect of 12- or 15-HETE on the levels of zonula occludens protein 1 (ZO-1), reactive oxygen species (ROS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
85
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 56 publications
1
85
3
1
Order By: Relevance
“…A large body of literature points out a link between oxidative stress and vascular diseases (62). A recent study showed that 12(S)-HETE increases retinal endothelial barrier permeability by NADPH oxidase-dependent reactive oxygen species production leading to phosphorylation and activation of VEGF receptor-2 (26). We have previously shown that 15(S)-HETE by activating nonreceptor tyrosine kinases, Src and Pyk2, stimulates ZO-2 tyrosine phosphorylation and its dissociation from claudins 1/5 and thereby disrupts aortic endothelial TJs in response to HFD feeding (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of literature points out a link between oxidative stress and vascular diseases (62). A recent study showed that 12(S)-HETE increases retinal endothelial barrier permeability by NADPH oxidase-dependent reactive oxygen species production leading to phosphorylation and activation of VEGF receptor-2 (26). We have previously shown that 15(S)-HETE by activating nonreceptor tyrosine kinases, Src and Pyk2, stimulates ZO-2 tyrosine phosphorylation and its dissociation from claudins 1/5 and thereby disrupts aortic endothelial TJs in response to HFD feeding (27).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it should be noted that studies from other laboratories have reported that deletion of the 12/15-LO gene reduces vascular permeability in a mouse model of acute lung injury (25). In addition, a recent report showed that 12(S)-HETE by NADPH oxidase-dependent reactive oxygen species production and VEGF receptor-2 tyrosine phosphorylation increases retinal endothelial cell permeability (26). Previously, we have demonstrated that 15(S)-HETE by stimulating ZO-2 tyrosine phosphorylation and its dissociation from claudins 1/5 disrupts endothelial TJs and its barrier function.…”
mentioning
confidence: 93%
“…Moreover, we have demonstrated in both human patients and animal models that retinal expression of 12/15-LOX is robustly induced during diabetes ( 21 ). At the same time, its pharmacological inhibition dampened the levels of infl ammatory cytokines, reactive oxygen species (ROS) gener ation, and phosphorylated VEGF receptor 2 expression in the retinas of diabetic mice ( 22 ). However, the cellular source of these lipid metabolites is unknown and could be derived from retinal tissues, including the retinal vascular endothelial, glial, and pigmented epithelial cells, as well as from infi ltrated infl ammatory cells.…”
Section: Animal Preparation and Experimental Designmentioning
confidence: 99%
“…Our recent study showed that inhibiting 12/15-LOX by baicalein reduced diabetes-induced ROS generation and NOX2 expression in mouse retina, suggesting the existence of an interconnected signaling between LOXs and NOX ( 22 ). However, the cross-talk between NOX and infl ammatory bioactive lipids remains ill-defi ned in DR.…”
mentioning
confidence: 99%
“…These authors concluded that free radicals generated by either COX or LOX pathways were responsible for the permeability response to AA. In a mouse model of diabetic retinopathy 12-HETE and 15-HETE, products of the lipoxygenase pathway, were shown to be responsible for increasing the permeability of retinal endothelial cell barrier via an NADPH oxidase-dependent mechanism [59]. Interestingly, AA inhibited the cytokine-induced up-regulation of several genes involved in endothelial cell inflammation [60].…”
Section: Fa Transport Across the Bbb And Effects Of Fa On Bbb Permeabmentioning
confidence: 99%